THE SEPARATION OF POWERS, ROLE OF THE PRESS AND THE EMERGENCE OF ONLINE MEDIA IN CHINA AND TAIWAN - Smith, Kaaden (Faculty of Law, Universitas Brawijaya, 2017)
Despite sharing a common culture over thousands of years, the modern stance of the Chinese and Taiwanese governments relating to the separation of powers and human rights has taken a drastically different path over the past seven decades. This paper begins with a brief introduction to traditional Chinese jurisprudence and how it has been shaped in recent times by the emergence of Western legal principles.It further examines the correlation between the separation of powers and the diversity of political discussion and level of regulation in the media of the People’s Republic of China (‘PRC’ or ‘China’) and the Taiwanese Republic of China (‘ROC’ or ‘Taiwan’), and how the constitutional and legislative provisions of each address these concepts and how they reflect international treaties adopted by each government. The emergence of online media to further demonstrate the different stances taken by the PRC and ROC on the adoption of these Western principles is analysed. Finally, the paper will examine the international criticisms the PRC and ROC face for their practices regarding media censorship. The paper suggests that maintaining a separation of powers is crucial in order to uphold a free, independent press.